The The Influence of SETS (Science, Environment, Technology, and Society) based E-Modules on Scientific Literacy Using the Discovery Learning Model - Elistiana, Veny; Novita, Nanda; Wahdi Ginting, Fajrul; Muliani; Fadieny, Nurul (Indonesian Journal of Technical and Vocational Education Training, 2024)
This research aims to identify the influence of SETS (Science, Environment, Technology, and Society) based e-modules in increasing scientific literacy using the discovery learning learning model. This research uses a quantitative approach with a quasi-experimental design in the form of a Nonequivalent Control Group Design. How to apply the sample using the Purposive Sampling technique where a total of 32 students were obtained consisting of 16 students in classes X1 and X2 as the control and experimental classes. The results showed that the average pretest score obtained by students in the experimental class was 29.68 and the average posttest score was 84.06, while in the control class the average pretest score obtained by students was 30.62 and the average score the posttest average was 69.68. Based on statistical test data using the independent sample test in SPSS Version 25, the results obtained were sig (2-tailed) 0.002 < significance 0.05, meaning that H0 was rejected and Ha was accepted. Where H0 is that there is no influence of SETS-based e-modules on students' scientific literacy and Ha is that there is an influence of SETS-based e-modules on students' scientific literacy.